The Role of EUPATI CH in Promoting Patient Involvement in Clinical Research: A Multi-Stakeholder Research Project - Sessa, Cristiana; Schmid, Caecilia; Tolotti, Angela; Magnin, Annette; Haerry, David; Bonetti, Loris; Klingmann, Ingrid (Frontiers in Medicine, 2021)
Background: The European Patients’ Academy on Therapeutic Innovation Switzerland (EUPATI CH) was established as an association in 2016 with the mission to improve patient empowerment in Switzerland, raise public awareness of EUPATI’s education material, and foster multi-stakeholder partnerships in order to promote public involvement in all aspects of medicines research and development (R&D). In order to achieve its goal of improving patient involvement (PI) in all processes of medicines R&D in Switzerland and to obtain guidance and recommendations for future activities, EUPATI CH initiated a multi-stakeholder survey on PI experiences, hurdles, and best practices. The survey enabled EUPATI CH to obtain and analyze the views of various stakeholders and shape its workplan. Methods: Data collection occurred between January and July 2019 using a survey and semi-structured interviews with individual stakeholders from different groups. The online survey responses were analyzed using quantitative methods and the interviews were analyzed using qualitative methods. Results: The online survey was completed by 55 respondents (10%), and the semi-structured interviews were conducted with 14 stakeholders. Respondents to the online survey were patient representatives (45%), researchers from academia (25%), individuals from the pharmaceutical industry (9%), healthcare professionals (23%), and representatives from government agencies (6%). Some respondents were also members of EUPATI CH. Thirty-eight percent of respondents consider PI in Switzerland to be limited or absent. They identified the main barriers to PI as, first and foremost, a lack of funds and human resources (65%), followed by a lack of information and a lack of education on how to become a patient advocate (21%), a lack of collaboration with other stakeholders (16%), and a lack of adequate resources. Respondents’ expectations of EUPATI CH’s role in supporting PI were to provide education for active PI and improve networking and collaboration among stakeholders. Conclusions: EUPATI CH’s multi-stakeholder research identified some of the difficulties in promoting PI in medicines R&D in Switzerland, in particular the complex collaboration among stakeholders and a lack of funds, human resources, and knowledge. To respond to these difficulties, EUPATI CH has begun preparing a basic training course for patients that is adapted to Switzerland.